The mental schemes and his influence in the aptitude to solve problems of learning for students of the National University Huánuco’s Hermilio Valdizán 2001 - Fonseca L., Abner (2009)
The intention of this research was to determine the types of mental schemes and the relation of these in the resolution of problems in the university students of UNHEVAL. The mental schemes were determined by a test of mental schemes that was applied to the students’ sample (69) in individual form and the resolution of problems was demonstrated using instruments to evaluate the cognitive thing, psicomotriz and affective actitudinal. 10 mental schemes were identified: Horizontal, Diagonal, Horizontal Vertical, Horizontal Diagonal, Horizontal Circular, Vertical Diagonal, Diagonal Circular, Horizontal Vertical Diagonal, Horizontal Circular Diagonal, Vague. The mental Horizontal scheme (57%), apparently, has major capacity for the resolution of cognitive problems; the mental Horizontal Vertical scheme (62%) has major capacity for the resolution of problems psicomotrices; and the mental Horizontal Diagonal scheme (85%) has major capacity for the resolution of problems Affective Actitudinales. The pupils of mental schemes who solve cognitive problems probably are more academic; the pupils of mental schemes who solve problems psicomotrices might be more skillful (right) in handicrafts; and the pupils of mental schemes who solve problems Affective Actitudinales have good treatment(deal) with the persons.